Laminar Natural Convection Heat Transfer Characteristics of Molten Salt Around Horizontal Cylinder. (May 2015) - Lu, Y.W.; Li, X.L.; Du, W.B.; Wu, Y.T.; Ma, C.F.
Abstract: In order to obtain the laminar natural convection heat transfer mechanism of molten salt, the natural convection heat transfer of multi-component molten salts around a cylinder with different diameters was studied by simulation. The result showed that the natural convective heat transfer of molten salt in the Rayleigh number range of 1.57×10-2 -2.03×106 cound be predicted by Fand's correlation that took the viscous dissipation into consideration, in addition to Prandtl and Rayleigh numbers. With the increasing in Rayleigh number, the effect of viscous dissipation decreased, so the other correlations that neglected the effect of viscous dissipation cound also predict the natural convection of molten salt well. Those results cound be a foundation for predicting the natural convection heat transfer of molten salt.